A systematic review of rice noodles: Raw material, processing method and quality improvement. (January 2021) - Li, Caiming; You, Yuxian; Chen, Di; Gu, Zhengbiao; Zhang, Yuzhu; Holler, Tod P.; Ban, Xiaofeng; Hong, Yan; Cheng, Li; Li, Zhaofeng
Abstract: Background: The increased consumption of rice noodle, a traditional rice-based product with high nutritional values and pleasant tastes, has led to increased research attention. Traditionally, rice noodle has been produced using a long series of steps including rice aging, rinsing, soaking, and milling, gelatinization, extruding/slitting, cooking, retrogradation, acid-pickling, drying, packaging, and sterilization. Current rice noodle production relies on semi-automatic techniques and lacks a comprehensive quality control system. This results in variable product quality that severely restricts the development of the rice noodle market. Scope and approach: In this article, the characteristics of the raw materials, the key processing steps of traditional and modern production methods, and the commonly used processing additives are reviewed to provide a reference point for the production of rice noodles with better flavor and improved quality. Key findings and conclusions: Rice noodle quality can be affected by numerous factors, including the species and compositions of rice, the pretreatment of raw materials, the processing methods, and the environmental conditions. Antiaging agents, water-retaining agents, and preservatives are also used as additives to improve rice noodle quality. Further studies are needed to explore the internal and external factors and mechanisms that affect the taste and storage quality of rice noodles. Improved processing methods and proper evaluation standards are needed to promote the standardization, mechanization, and automation of rice noodle production. Highlights: The classification and characteristics of different rice noodles are summarized. Key processes in traditional and modern production of rice noodles are presented. Factors affecting the taste and storage qualities of rice noodles are discussed. Antiaging agents, water-retaining agents, preservatives are mainly used additives.